Efficacy of exogenous surfactant during conventional and highfrequency oscillatory ventilation in preterm infants with RDS - Vento, G.; Tana, M.; Tirone, et al., C. (Acta Biomedica Atenei Parmensis, 2013)
Introduction: The immediate effects of exogenous surfactant on lung volume and hemodynamics in preterm infants have been poorly studied. Materials and Methods: Lung volume, SpO2, perfusion index, regional SO2, transcutaneous partial pressure of CO2 were simultaneously monitored and recorded ten minutes after surfactant tracheal instillation in elective HFOV ventilated preterm infants with RDS. Outcomes: Despite a reduction in gas exchange during the first 5 minutes post surfactant instillation, most likely dependent on airway obstruction, lung volume increases rapidly in HFOV preterm infants with RDS. After 5 minutes from administration of surfactant, lung volume, gas exchange and PI reach stable values and CDP can be safely reduced.